An Efficient Approach for the Synthesis of 1, 1‐bis(2‐phenyl‐3‐indolyl)ethylene Using ZnO Nanocatalyst. (5th December 2017) - Madan, Yogita; Gupta, Ragini
Abstract : A combination of nanocatalyst and green chemical route (mechanochemistry) was used to generate a series of substituted 1, 1‐bis(2‐phenyl‐3‐indolyl)ethylene derivatives (4a–e ) that were synthesized by reacting various 2‐arylindoles (1a–e ) and acetyl chloride in absolute alcohol with or without ZnO nano as catalyst via two approaches, that is, classical and green solvent‐free route. The use of ZnO nano particles is preferred to absence of catalyst in terms of short reaction time and mild reaction conditions with reusability of the catalyst. All the synthesized compounds were characterized on the basis of their elemental and spectral data (IR, proton magnetic resonance, 13 C NMR, and Mass). Abstract :